Three new species of Acanthobothrium Blanchard, 1848 (Cestoda:Onchoproteocephalidea) in Stingrays (Dasyatidae) from the Pacific coast in Mexico - Zaragoza-Tapia, Francisco; Pulido-Flores, Griselda; Monks, Scott (Zootaxa, 2020)
Three new species of Acanthobothrium Blanchard, 1848 (Onchoproteocephalidea: Onchobothriidae) are described from Pacific coastal waters of Mexico. Based on four criteria for categorization of species of Acanthobothrium, the three new species belong to Category 2 species, characterized by their total length (< 15 mm), number of proglottids (< 50) and testes (<80), and with asymmetrical ovary. Acanthobothrium ppdeleoni n. sp. from diamond stingray Hypanus dipterurus (Jordan & Gilbert) is differentiated from congeners by a combination of characters including total length of the whole worms, size of the scolex and bothridia, length of the bases of the hooks and abaxial prongs, and the size of the cirrus sacs in mature proglottids. Acanthobothrium hypanus n. sp. and A. sinaloaensis n. sp. are described from longtail stingray Hypanus longus (Garman). Acanthobothrium hypanus n. sp. is differentiated by a combination of characters including size of the scolex and bothridia, diameter of the accessory sucker, length of the abaxial prongs, size of the cirrus sacs and testes in mature proglottids. Acanthobothrium sinaloaensis n. sp. is differentiated by a combination of characters including size of the scolex and bothridia, diameter of the accessory sucker, size of the cirrus sacs in mature proglottids, number of immature proglottids, number of testes, the length of the lobes of the ovary and the absence of velum between medial margin of bothridia. Thirteen species of Acanthobothrium have been reported previously from elasmobranchs from the Pacific coast of Mexico. In the present study, the number of species is elevated to 16.